Model for End-stage Liver Disease (MELD) in spontaneous bacterial peritonitis –a clinical study at a tertiary health center in Nepal - Pathak, Rahul; Niraula, Kiran; Khadga, Prem Krishna; Singh, Kumar Vikram; Sharma, Ishwar (Journal of Advances in Internal Medicine, 2013)
Background and Aims: The aim of this study was to assess the predictive value of different variables including the Model of End-stage Liver Disease (MELD) scores in hospitalized patients with spontaneous bacterial peritonitis (SBP) and its correlation with adverse outcomes. Methods: A cross-sectional study of 73 patients diagnosed with cirrhosis, ascites, and spontaneous bacterial peritonitis admitted to a gastroenterology department from February 2010 to November 2012. MELD scores were calculated using laboratory parameters and the United Network of Organ Sharing (UNOS) internet MELD tool. Results: Categorical variables and mortality status were analyzed for association by chi-square test. MELD scores and all-cause mortality were found to be positively correlated. Mortality was higher among the groups with MELD scores greater than 15. Upon stratification of the groups by mortality status, only age and urea level were novel and consistent predictors of mortality. Conclusions: In this Nepalese sample of cirrhotic patients, MELD scores along with age and urea level were confirmed as significant predictors of mortality. DOI: http://dx.doi.org/10.3126/jaim.v2i2.8776 J ournal of Advances in Internal Medicine 2013;02(02):47-51